Предмет: Химия,
автор: indira9696
Fe2(SO4)3 - Fe(OH)3 - Fe2O3 - Fe2(SO4)3
Ответы
Автор ответа:
0
1) Fe2(SO4)3 + 3Ba(OH)2 → 2Fe(OH3)(бурый осадок) + 3BaSO4
2) 2Fe(OH)3 →(при нагревании) Fe2O3 + 3H2O
3) Fe2O3 + 3H2SO4(разбавленная) → Fe2(SO4)3 + 3H2O
2) 2Fe(OH)3 →(при нагревании) Fe2O3 + 3H2O
3) Fe2O3 + 3H2SO4(разбавленная) → Fe2(SO4)3 + 3H2O
Похожие вопросы
Предмет: Математика,
автор: pichdyr
Предмет: Математика,
автор: Аноним
Предмет: Английский язык,
автор: ghjgghh
Предмет: Математика,
автор: idk2002